Food habits of horses, cattle, and sheep-goats and food supply in the forest–steppe zone of Mongolia: A case study in Mogod sum (county) in Bulgan aimag (province). (March 2020) - Takatsuki, Seiki; Morinaga, Yuki
Abstract: According to the social changes in the 1990s, livestock population in Mongolia is rapidly increasing, resulting in overgrazing and subsequent degradation of the grasslands. However, little is known about the quantitative food habits of Mongolian livestock. We evaluated the food habits of horses, cattle, and sheep and goats in the forest–steppe zone of northern Mongolia by fecal analysis. We compared fecal compositions at a valley (Place 1) and a riverside (Place 2). Place 1 consisted mainly of Stipa -dominated slopes (93%) while Place 2 comprised Stipa -dominated slopes (77%) and Carex -dominated alluvial flats (23%). Horse feces were dominated by graminoids (60%–70% graminoids), with a high percentage of Carex (30%–40%). Stipa accounted for about 20%–40% in the cattle feces. Sheep and goat feces contained about 30% Stipa and about 40% culms. These results suggest that the food habits of the livestock were affected more by animal characteristics than habitats. The high Carex content in the horse feces occurred because horses roamed freely and could visit Carex swards. Cattle moved near the gers (tent houses) and returned every evening, and it was difficult for them to visit far away Carex swards. Sheep-goats were herded and often grazed on steeper slopes than cattle and horses, explaining the large proportion of culms and small proportion of Carex in the feces. Quantitative food habit studies of livestock is useful for the grassland management of arid regions. Highlights: Horses selectively fed on sedges, growing at humid habitats. Cattle non-selectively fed on Stipa leaves which were most abundant. Foods of sheep and goats were similar to those of cattle. Foods of livestock were more affected by livestock types than places.